Surgical outcomes of manual small incision cataract surgery in colobomatous eyes at a tertiary referral center: A prospective observational study - Sapkota, Anjana; Patel, Sushila; Thakali, Ashwin (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Coloboma is a congenital ocular defect affecting various ocular structures and can make cataract surgery more challenging. Evidence on surgical outcomes from developing regions remains limited. This study evaluated the outcomes of manual small incision cataract surgery (M-SICS) in colobomatous eyes at a tertiary center.Methods: This prospective analytical study included 46 eyes with congenital coloboma and visually significant cataract managed at a tertiary referral center. Preoperative assessment included visual acuity, slit lamp examination, and biometry. The surgical technique was primarily M-SICS. Patients were followed on postoperative day 1, at 2 weeks, and 6 weeks. Outcomes assessed included visual acuity, intraoperative events, and postoperative complications. Statistical analysis included paired t-test and repeated measures ANOVA.Results: The mean age was 43.37±1.7 years, with 52.2% females. Bilateral involvement was present in 56.5%. Microcornea was observed in 39.1% and macula sparing coloboma in 65.2%. Preoperative mean visual acuity was 1.528±0.614 LogMAR, with 65.2% presenting with BCVA ≤1/60. Intraoperative challenges included poor pupillary dilatation in 45.7% and zonular weakness in 32.6%. Posterior capsular rent occurred in 23.9%. Intraocular lens implantation was achieved in 80.4%. Postoperatively, visual acuity improved significantly to LogMAR 0.996 on day 1, 0.720 at 2 weeks, and 0.696 at 6 weeks. Significant improvement was seen at all time points, p < 0.001. Good visual outcome was achieved in 58.7%. Corneal edema resolved by 6 weeks.Conclusions: M-SICS provides effective visual rehabilitation in colobomatous eyes despite intraoperative challenges.